The Effect of Mathematics and Physical Science on Matriculants’ Overall Performances: Analysis Using Multilevel Model - Letsoalo, M. E. (Journal of Education and Vocational Research, 2018)
This comparative, cross-sectional, quantitative and ex-post-facto designed study used secondary and correlated data to compare the likelihood of passing matric between learners from Gauteng and Western Cape provinces, even after adjusting for subject-type. This study attempted to assess the relation between school resources input, subject offered, learner’s gender and learners’ academic achievements. The data used in this study were supplied by the Umalusi Council. The dataset contained 145783 matric learners (65245 [44.75%] males and 80538 [55.25%] females) who wrote the matric examinations in Gauteng and Western Cape provinces in November 2009. The unadjusted model indicated that learners in Western Cape were significantly 1.193 more likely to pass matric than learners in Gauteng province (p < 0.001, OR = 1.193, 95%CI: 1.164 - 1.223). The adjusted model results indicated that learners in the Western Cape province were 1.5122 more likely to pass matric when compared to learners in Gauteng province (p < 0.001, OR = 1.512, 95%CI: 1.471 - 1.555). These results indicate that the odds of passing matric, after adjusting for science subjects, increased in favour of learners in the Western Cape Province. It can be concluded that the Western Cape Province provides more enabling conditions to ensure matriculants’ superior performance. It is suggested the strategies to improve the quality of mathematics and science educators need to be implemented, especially in Gauteng province. Also, the policy that advocates for the differentiation approach should be adopted, as opposed to the current policy that advocates for a more general, rigid approach that does not recognise the inherent differences in the provinces.